The structural, morphological, and surface properties of tungsten-doped TiO2 nanopowders and their contribution to the photocatalytic activity - Park, Bo-In; Jie, Hyunseock; Song, Bong-Geun; Kang, Kae-Myung; Park, Jong-Ku; Cho, So-Hye (SPRINGER, 2014)
Tungsten-doped TiO2 nanopowders (W-TiO2) were prepared by chemical vapor synthesis and the effects of a post-heat treatment on their physical, surface, and photocatalytic properties were investigated. The W-TiO2 nanopowders containing about 1.0 mol % of tungsten were obtained and annealed from 400 to 700 degrees C. The as-synthesized and annealed W-TiO2 nanopowders were carefully examined for their crystalline and opto-electronic structure and morphology by means of X-ray diffraction, UV-Vis spectroscopy, and transmission electron microscopy. In addition, the surface condition was investigated by X-ray photoelectron spectroscopy. The photocatalytic activities were studied by the oxidative degradation of 2-propanol under UV light irradiation. We found that the photocatalytic activity of W-TiO2 varied significantly with the temperature of the heat treatment, exceeding the performance of P25 after annealing at 600 degrees C. Interestingly, the chemical composition of titanium and tungsten of W-TiO2 played a crucial role to its photocatalytic activity as the mixed valence states, Tin+ (n = 4, 3, 2, 0) and Wn+ (n = 6, 5, 4), were found in accordance with altering the annealing temperature.
Keywords: HYDROTHERMAL TREATMENT; LIGHT IRRADIATION; TITANIUM-DIOXIDE; ENHANCEMENT; DEGRADATION; CATALYSTS; SOL; WO3; UV